(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines phase verbs in the German language as a specific group of verbal means used to express different stages of an action or process. The study focuses on the semantic and syntactic characteristics of phase verbs as well as their functional role in modern German. Special attention is paid to the classification of phase verbs and their interaction with infinitive constructions. The analysis is based on examples taken from contemporary German literary texts, journalistic sources, and grammatical descriptions. The results demonstrate that phase verbs play an important role in structuring temporal and aspectual meanings and contribute to the clarity and precision of verbal expression. The findings may be useful for further research in German grammar, contrastive linguistics, and language teaching.